Patient Satisfaction with Doctor-Patient Interaction using SKIP-11 and Its Associated Factors among Type 2 Diabetics in Primary Care. - Mohd Yusoff, Siti Suhaila; Pah Kiam , George Wong; Yaacob, Lili Husniati; Draman, Nani (IIUM Medical Journal Malaysia, 2021)
ABSTRACT Introduction: The quality of diabetes care is widely suboptimal, and most of the interventions depend on the active involvement and participation of patients. Understanding and determining patient related factors can help primary care providers pay more attention and give greater care to those patients. This will improve patient satisfaction, which further enhances compliance with or adherence to diabetic treatment. Therefore, this study aims to determine patient satisfaction with doctor-patient interaction and its associated factors among patients with type 2 diabetes mellitus. Materials and Methods: This cross-sectional study was performed among adults who had had diabetes for at least six months. Participants were selected by systemic random sampling in the outpatient clinic of the University Hospital. Patient satisfaction with doctor-patient interaction was measured using 11- items with a three-domain version of the “Skala Kepuasan Interaksi Perubatan-11” questionnaire. The total scores ranged from 11 to 55, and those who scored 44 and above (> 80%) were considered satisfied. Results: A total of 417 patients were recruited in the study. 60% were satisfied with their doctor-patient interactions. Among the subtypes in the satisfied group, the domain of rapport had the highest percentage of satisfaction at 77.7%. HbA1c was found to be significant associated with patient satisfaction with doctor-patient interaction (95% CI: 0.81, 0.97; p = 0.008) Conclusion: 60% of the participants clearly illustrated positive feedback and were more satisfied with their doctor-patient interactions. HbA1c was found to be significantly associated with patient satisfaction concerning doctor-patient interaction